Aportes de la historia de la ciencia a la construcción de explicaciones en el aula - Paredes-Arturo, Nayibe-Mabel; García-Martínez, Álvaro (Revista Científica, 2021)
This paper presents the results of a study conducted with a group of natural science teachers in service of Institución Educativa Libertad (Pasto, Nariño). Its objective was to analyze the design of activities elaborated by teachers when explaining the combustion phenomenon in the context of a school, making use of the Faraday’s The chemical history of a candle, a historical case. The methodology is qualitative, with an interpretative approach and a multiple case study. A professional development community (PRODEC) was created with the teachers, who participated in teacher training workshops. The survey and the written production of the designs created by the teachers were used as instruments. The information was systematized with Atlas.ti, and the explanations from the content analysis were studied according to four categories: contextual elements, structuring, transference, and metacognitive reflection. It was evident that the contributions of the historical case in the construction of explanations were oriented in two directions: the first, with respect to the explanation of the combustion phenomenon in the classroom; and the second, regarding the strategies for the explanation of science to young people.